THE INFLUENCE OF PRODUCT INNOVATION AND SOCIAL MEDIA MARKETING ON MIRACLEMATES BRAND PURCHASE DECISIONS - Didi Tarmidi; M. Aqsal Alghifary (Jurnal Ekonomi, 2022)
The study aims to determine the magnitude of the influence of product innovation and social media marketing on purchasing decisions at the Miraclemates fashion brand in the city of Bandung. Miraclemates is trying to expand sales, one of which is utilizing social media. The research method uses quantitative methods with 100 respondents of social media users in the city of Bandung which are then analyzed using multiple regression processed with the help of SPSS25 software. The main data from the study used a questionnaire survey, and secondary data were obtained through the publication of journals, articles, and theoretical books. The results of this study show that the variables of product innovation and social media marketing affect miraclemates' purchasing decisions. The amount of product innovation and social media marketing affecting purchasing decisions is 35.6%.